Determinants of technological innovation in Argentina and Brazil - Eduardo Gonçalves; Mauro Borges Lemos; João de Negri (CEPAL Review, 2008)
This article analyses and compares the determinants of innovation in Argentina and Brazil, countries that have based their industrialization strategies on import substitution. Probit regressions in which instrumental variables are used to check for problems of endogeneity of exports reveal that, in both countries, knowledge external to firms helps to promote innovation, that internal research and development capacity is relatively weak and that external trade integration has a positive effect on firms’ propensity to innovate (more so in Brazil than in Argentina). The results of this study suggest in general that there has been modest progress in the pattern of innovation among Argentine and Brazilian firms in recent years compared with the import substitution period.